Spectral Photon-counting cT: Initial Experience with Dual-Contrast Agent K-Edge Colonography - Muenzel, Daniela; Bar-Ness, Daniel; Roessl, Ewald; Blevis, Ira; Bartels, Matthias; Fingerle, Alexander A.; Ruschke, Stefan; Coulon, Philippe; Daerr, Heiner; Kopp, Felix K.; Brendel, Bernhard; Thran, Axel; et al. (Radiology, 2017)
Purpose: To investigate the feasibility of using spectral photoncounting computed tomography (CT) to differentiate between gadolinium-based and nonionic iodine-based contrast material in a colon phantom by using the characteristic k edge of gadolinium. Materials and A custom-made colon phantom was filled with nonionic Methods: iodine-based contrast material, and a gadolinium-filled capsule representing a contrast material-enhanced polyp was positioned on the colon wall. The colon phantom was scanned with a preclinical spectral photon-counting CT system to obtain spectral and conventional data. By fully using the multibin spectral information, material decomposition was performed to generate iodine and gadolinium maps. Quantitative measurements were performed within the lumen and polyp to quantitatively determine the absolute content of iodine and gadolinium. Results: In a conventional CT section, absorption values of both contrast agents were similar at approximately 110 HU. Contrast material maps clearly differentiated the distributions, with gadolinium solely in the polyp and iodine in the lumen of the colon. Quantitative measurements of contrast material concentrations in the colon and polyp matched well with those of actual prepared mixtures. Conclusion: Dual-contrast spectral photon-counting CT colonography with iodine-filled lumen and gadolinium-tagged polyps may enable ready differentiation between polyps and tagged fecal material.
CRIS-Team Scopus Importer:2023-03-08